Study of the function of Thyroid gland in β- thalassemia major male patients in Kirkuk city. - Mossa M. Marbut; Bassam Saleh Jameel; Amina H. Hamed; Issa H. Kareem (Journal of Madenat Alelem University College, 2016)
Thalassemia has been classified by the world health organization as a major public health problem. Itoccurs throughout the world and regarded as one of the major health problems in endemic regionsas Middle East, Mediterranean countries, Asia and North Africa. Endocrine complications inThalassaemia Major Patients with multitransfused Thalassaemia Major patients may develop severeendocrine complications. Due to multiple transfusions is the main cause of such complications, Ironaccumulates in many tissues such as liver, heart and endocrine glands. The study aims to study thefunction of Thyroid gland in β- thalassemia Major male patients in Kirkuk city. The study wasconducted β-thalassaemia major patients whom attended the thalassaemia center in Azadi Teachinghospital in Kirkuk Governorate from September 2015 to the end of January 2016. A total of 105 malesubjects were participated in the study, (30 normal healthy subjects and 75 thalassaemic patients).Body weight height was measured. About, five ml of venous blood were obtained from all normalsubjects and patients. One ml of blood sample was collected for measurement of packet cell volume(PCV) and heamoglobin (Hb). The remaining four ml of blood sample were used for serumseparation. Serum used for measurement of serum thyroid stimulating hormones (TSH), T3 and T4.Results of study showed a high significant decrease in body weight and height of male thalassemicpatients as compare with male counterpart of control subjects of same age. Also, there was a highlysignificant reduction in the concentration of heamoglobin and PCV value in thalassaemic malepatients as compared with control male subjects. There is no significant increase in serum Thyroidstimulating hormone (TSH) concentration in male thalassemic patients as compare with male controlsubjects. However, there is highly significant reduction in serum T4 and T3 concentrations in malethalassemic patients as compare with male control subjects.